254-OR: Effects of Roux-en-Y Gastric Bypass on Postprandial Glucose Turnover Assessed through the Single-Tracer Oral Minimal Model - BRUNASSO, ALESSANDRO; DALLA MAN, CHIARA; HERZIG, DAVID; BALLY, LIA; SCHIAVON, MICHELE (Diabetes (New York, N.Y.), 2023)
Rearrangements of gastrointestinal anatomy after Roux-en-Y gastric bypass (RYGB) surgery alter postprandial glucose metabolism. However, the impact on different components of glucose homeostasis remain incompletely understood. Here, we aim to evaluate the effects of RYGB on postprandial glucose turnover, production (P) and disposal (D) glucose effectiveness (GEP, GED) and production and disposal sensitivity to insulin (SIP, SID). Ten RYGB (2M, age=39.2±3.1 y, BMI=28±1 kg/m2- mean±SE) subjects and 10 healthy controls (5M, age=36.4±3.2 y, BMI=26±1 kg/m2) ingested 60g of glucose (G) labelled with [6,6-2H2]-glucose. Plasma samples were frequently drawn to measure G, insulin (I) and tracer concentrations in the following 180 min. The Single-Tracer Oral Minimal Model was used to estimate meal glucose rate of appearance (Ra), endogenous glucose production (EGP), glucose disposal (Rd), GEP, GED, SIP and SID. Incremental area under the G curve (iAUC(G)) was not different in the two groups, while iAUC(I) was significantly higher in RYGB (8346±803 vs. 5451±602 μU/mL*min, p=0.011); iAUC(Ra) normalized to the G dose was significantly higher in the first 60 min after the meal (0.72±0.04 vs. 0.28±0.03, p<0.001) while, throughout the experiment, EGP suppression (EGPs) normalized to basal (EGPb) was significantly lower (0.31±0.06 vs. 0.55±0.05, p=0.006) and iAUC(Rd) normalized to basal (Rdb) was higher (3.46±0.10 vs. 2.82±0.08, p<0.001) in RYGB than controls. Model predicted SIP was significantly lower in RYGB than controls (2.0±0.5 vs. 5.1±1.2 10-4 dL/kg/min per μU/mL, p=0.033) while no differences were observed in GEP, GED and SID. We concluded that the abnormally high I concentration in RYGB was responsible for the higher iAUC(Rd) in the operated individuals, while the reduced SIP likely works as a protective mechanism against postprandial hypoglycaemia by reducing EGPs despite the high circulating I.